Earthworms and microorganisms: disentangling the black box of vermicomposting. - Aira, Manuel; Domínguez, Jorge (Instituto de Ecología, A.C., 2010)
Earthworms affect microorganisms both directly (enhancing or reducing their populations by digesting the substrate) and indirectly (derived effects, such as the production of castings in the fresh substrate). To separate these effects we performed three experiments. In the first, we studied the whole process of vermicomposting, using Eisenia fetida and pig manure in all stage, from fresh residue to vermicompost. In the second experiment, we inoculated pig manure with vermicompost to study the indirect effects of earthworms on decomposition. In the third, we analysed the fresh casts to study direct effects of earthworms on microorganisms. Earthworms promoted significant increases in both microbial biomass and activity when they were present in the layers, and in aged layers where earthworm were absent, microbial stabilization occurred, with reduced biomass and activity. Inoculation with vermicompost produced the same increases in microbial biomass and activity, and although these increments were not as high as in presence of earthworms, indirect effects were strong enough to alter the dynamics of organic matter decomposition. In castings, microbial biomass increased, while activity decreased, suggesting the presence of other factors involved in earthworm-microbial relationships, beyond simple digestion and inoculation effects.